The prevalence of burnout and depression among medical doctors working in the Cape Town Metropole community health care clinics and district hospitals of the Provincial Government of the Western Cape : a cross-sectional study - Rossouw, Liezel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMed)--Stellenbosch University, 2011.